Elemental abundance study of the CP star HD 206653 - Albacete-Colombo, J.F. (2002)
An analysis of the abundances of the Silicon star HD 206653 is presented using an ATLAS9 model atmosphere and observational material taken with a REOSC echelle spectrograph attached to the Jorge Sahade 2.15 m telescope at CASLEO. The light elements are solar or deficient except silicon which is overabundant by a factor of 5. The iron peak elements are all overabundant by factors between 10 and 50. Sr and Y are around 1000 times the solar values. Among the Rare Earths only Ce and Eu are identified; both are overabundant by large factors.